**Multiplying Polynomials by Monomials**

**4 (2 + 4) = 4 (6)****= 24**

*4 (2 + 4) = 4(2) + 4(4)*

*= 8 + 16*

*= 24*

*5 (6-3) = 5(3)*

*= 15*

*5 (6 -3) = 5(6) -3(5)*

*= 30 - 15*

*= 15*

*2x (3x + 4)*

*2x (3x + 4) = 2x(3x) +2x(4)*

*= 2(3)(x)(x) + 2(4)(x)*

*= 6 x^2 + 8x*

*5 x (-2x +y -2)*Now I'll show you how to do the reverse. Finding the equation when you have the diagram.

Remember that the first part of the polynomial is on the left side of the diagram.

In this case ** -2x **is the first part.

**is the other part.**

*3x -4*So the formula is *-2x (3x - 4)*

Now we solve!

*-2x (3x -4) = -2x (3x) - 4 (-2x)*

*= -6x^2 + 8x*

Some common mistakes people make when multiplying polynomials by monomials is...

1. Forgetting to look at the signs. Instead of making a number negative, you make it positive and vice versa

2. You forget to multiply all the terms in a polynomial. This one is kind of self-explanatory. REMEMBER TO MULTIPLY ALL THE TERMS!

Okay people! Here's the homework.

- Read Pages 264 -268
- Check your Understanding 2 and 3
- Practise 0dd or even
- Apply All
- Extend 2 of 3
- And the 7.4 Green sheet we got ages ago.
- And last but certaionly not least... MANGAHIGH!!! We are in a Fai-To!!!

If you have questions please ask. If not, then I bid you *adieu.*

Oh yeah I almost forgot. The next blog person is......... ANA LOPENA

## No comments:

## Post a Comment